Using Lipid Parameters in Predicting Preterm Infants with Respiratory Distress Syndrome - Mahmoud Silema, Ebtessam Mohammed (Clinical Medicine And Health Research Journal, 2024)
Background: Respiratory distress syndrome is a clinical diagnosis which is warranted in a preterm newborn with respiratory difficulty, including tachypnea (>60 breaths/min), chest retractions, and cyanosis in room air that persist or progress over the first 48-96 hr of life, and a characteristic chest radiographic appearance. Objective: to assess the cord blood lipid profile for predicting of preterm infants with respiratory distress syndrome. Methods: This is a case control study which was conducted on 50 preterm neonates admitted to the neonatal intensive care unit of Shebin El-Kom teaching hospital between January 2011 and October 2011. Results: the mean of weight gain during pregnancy in mothers of preterm with RDS was lower than the control group and the difference was statistically highly significant (P<0.01). Also, there was significant difference (P<0.05) regarding mode of delivery and antenatal steroid, however; no statistical significant difference was detected regarding maternal age, maternal weight, maternal BMI, pre-gravid height, the ruptured membrane > 24 hr and parity between both groups. the mean of total cholesterol, HDL-cholesterol and LDL-cholesterol in the cord blood was lower in group A than in group B and the difference was statistically highly significant (P <0.01), but there was no significant difference regarding the mean of both triglycerides and VLDL-cholesterol in both groups (P>0.05).the mean of total cholesterol, HDL-cholesterol and LDL-cholesterol was lower in mothers of preterm infants with RDS than in control group and the difference was statistically highly significant (P <0.01), but there was no significant difference was detected regarding the mean of levels triglycerides and VLDL-cholesterol in both groups (P >0.05).the cutoff values of cord blood (total Cholesterol, HDL-C, and LDL-C) below which RDS can be predicted are 80, 45.5 and 23.2 mg/dl respectively with a sensitivity of 83.3%, 86.7% and 86.7% and with specificity of 95%, 80% and 70% respectively. Conclusion: We conclude that RDS is accompanied with lipid alteration in the infants and their mothers. The results of this study point to the importance of measuring of maternal serum and cord blood lipid profile as a predictor for the occurrence of RDS.